THE RELATIONSHIP BETWEEN OBESITY WITH RISK INCIDENT OF OBSTRUCTIVE SLEEP APNEA - Fakhruddin, Helmi; Aphridasari, Jatu; Hastuti, Heni (Nexus Kedokteran Klinik, 2016)
Introduction : The purpose of this research is to determine the relationship between obesity and risk incident of Obstructive Sleep Apnea (OSA). This research was conducted at the Medical Faculty Sebelas Maret University of Surakarta from October 2015 to November 2015. Methods : This research was an analytical research using cross sectional approach. The size of population was 200 while the size of sample was 100 people. The sampling techniques usedÂ  purposive random sampling. The data were obtained by questionnaire, research instrument with a guided interview technique using weighting machine, and microtoise. The obtained data were presented in tabular form and analyzed using the Chi Square Test at the level of significance Î± = 0,05. Results : From the result of research conducted in the Medical Faculty of Sebelas Maret University Surakarta from October 2015 to November 2015, it was obtained that subjects with obesity who had high risk of OSA was 29 people (78%). This number was more than the number of subjects with obesity who had low risk of OSA of 21 people (33%) from the total of 50 subjects with obesity. While the number of subjects who didnât have obesity with high risk of OSA was 8 people (22%).Â  This number was fewer than the number of subjects who didnât have obesity with low risk of OSA of 42 people (67%).Â  The results of data analysis obtained X2= 18,198 and OR= 7,25; so that it could be concluded statistically, that there was a relationship between obesity and risk incident of OSA. Conclusions : The conclusion from this research was there was relationship between obesity and risk incident of Â OSA. Keyword: ObesityÂ  âÂ  Obstructive pulmonary diseaseÂ  â Obstructive Sleep Apnea (OSA)